Whole-exome sequencing as a diagnostic tool for distal renal tubular acidosis - Paula Cristina Barros Pereira; Flávia Medeiros Melo; Luiz Armando Cunha De Marco; Eduardo Araújo Oliveira; Débora Marques Miranda; Ana Cristina Simões e Silva (Elsevier, 2015)
Objective: Distal renal tubular acidosis (dRTA) is characterized by metabolic acidosis due to impaired renal acid excretion. The aim of this study was to demonstrate the genetic diagnosis of four children with dRTA through use of whole-exome sequencing. Methods: Two unrelated families were selected; a total of four children with dRTA and their parents, in order to perform whole-exome sequencing. Hearing was preserved in both children from the first family, but not in the second, wherein a twin pair had severe deafness. Whole-exome sequencing was performed in two pooled samples and findings were confirmed with Sanger sequencing method. Results: Two mutations were identified in the ATP6V0A4 and ATP6V1B1 genes. In the first family, a novel mutation in the exon 13 of the ATP6V0A4 gene with a single nucleotide change GAC → TAC (c.1232G>T) was found, which caused a substitution of aspartic acid to tyrosine in position 411. In the second family, a homozygous recurrent mutation with one base-pair insertion (c.1149_1155insC) in exon 12 of the ATP6V1B1 gene was detected. Conclusion: These results confirm the value of whole-exome sequencing for the study of rare and complex genetic nephropathies, allowing the identification of novel and recurrent mutations. Furthermore, for the first time the application of this molecular method in renal tubular diseases has been clearly demonstrated. Resumo: Objetivo: A acidose tubular renal distal (ATRd) é caracterizada por acidose metabólica devido a excreção renal de ácido prejudicada. O objetivo deste artigo é apresentar o diagnóstico genético de quatro crianças com ATRd utilizando o sequenciamento total do exoma. Métodos: Selecionamos duas famílias não relacionadas, totalizando quatro crianças com ATRd e seus pais, para realizar o sequenciamento total do exoma. A audição foi preservada em ambas as crianças da família um, porém em nenhuma criança da família dois, na qual um par de gêmeas teve perda auditiva severa. Realizamos o sequenciamento total do exoma em dois conjuntos de amostras e confirmamos os achados com o método de Sequenciamento de Sanger. Resultados: Duas mutações foram identificadas nos genes ATP6V0A4 e ATP6V1B1. Na família um, detectamos uma nova mutação no éxon 13 do gene ATP6V0A4 com uma alteração em um nucleotídeo único GAC → TAC (c.1232G>T) que causou substituição de ácido aspártico por tirosina na posição 411. Na família dois, detectamos uma mutação recorrente do homozigoto com inserção de um par de bases (c.1149_1155insC) no éxon 12 do gene ATP6V1B1. Conclusão: Nossos resultados confirmam o valor do sequenciamento total do exoma para o estudo de nefropatias genéticas complexas, permitindo a identificação de mutações novas e recorrentes. Adicionalmente, demonstramos claramente pela primeira vez a aplicação desse método molecular em doenças tubulares renais. Keywords: ATP6V0A4, ATP6V1B1, Children, Distal renal tubular acidosis, Genetics, Whole-exome sequencing, Palavras-chave: ATP6V0A4, ATP6V1B1, Crianças, Acidose tubular renal distal, Genética, Sequenciamento total do exoma